Materiales para la enseñanza del portugués en España y del español en Portugal: contextos de aparición y divulgación - Ponce de León Romeo, Rogelio (2020)
The aim of this paper is to study all the grammars and manuals -located to date- that were published in Portugal for learning Spanish and in Spain for learning Portuguese from 1848 to 1960. We propose an analysis -new, regarding the classification of these materials- taking as reference certain variables that have to do with the pedagogical context of dissemination and edition of manuals, as well as with the sociopolitical one; especially the influence of certain government decisions, with a view to the cultural and political approach of Spain towards Portugal in the mid-20th century, with consequences on the spread of Portuguese language in Spain and Spanish language in Portugal.